THE RELATIONSHIP BETWEEN HYPOTHYROIDISM AND CARDIOVASCULAR DISEASES - Axmadulina , Galiya (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
Hypothyroidism is a common endocrine disorder characterized by a decrease in thyroid hormone levels, which significantly affects various body systems, including the cardiovascular system. This article examines the main mechanisms of the influence of hypothyroidism on the functioning of the heart and blood vessels. It has been established that thyroid hormone deficiency leads to decreased myocardial contractility, increased peripheral vascular resistance, and disturbances in lipid metabolism. These changes contribute to the development of atherosclerosis, arterial hypertension, and coronary heart disease. The analysis of scientific sources has shown that both overt and subclinical hypothyroidism may increase the risk of cardiovascular complications. Timely diagnosis and adequate hormone replacement therapy play an important role in preventing and reducing the risk of cardiovascular diseases in patients with hypothyroidism.